Banking on the future of rock outcrops: analysis and comparison of soil seedbanks and extant aboveground vegetation composition of two high elevation communities - Blackburn, Amanda-Jean (2021)
The Southern Appalachian Mountains are an ancient region that supports an assortment of rare high-elevation communities. Rock outcrops are understudied communities that support a rich biodiversity of rare and endemic species and alpine relicts’ representative of the Pleistocene. Rock outcrop communities can be classified into different types, but the two addressed in this study are montane red cedar outcrops (MRC, defined by the presence of Juniperus virginiana), and non-red cedar outcrops (NMRC, lacking Juniperus virginiana). These precariously balanced communities are strongly threatened by habitat destruction, air pollution, and global warming; increased knowledge of the biodiversity and biogeography of flora will aide in conservation and management efforts. Understanding the soil seed bank and its similarity to the aboveground vegetation is imperative to truly evaluate the differences in species diversity; processes affecting species composition such as environmental filtering, and seed dispersal and recruitment between outcrop types. Soil core samples were taken in Spring 2020 from 3 MRC and 3 NMRC rock outcrops and utilized in a combined direct seedling emergence and counting experiment to analyze species abundance and diversity within the soil seed bank. Herbaceous flora on the same sites was inventoried over two summer months to determine similarity between the soil seed bank and the extant aboveground vegetation on MRC and NMRC sites. Overall, both MRC and NMRC sites displayed high soil seedbank and aboveground vegetation species diversity. The results indicate wide variation in the soil seedbank composition of both MRC and NMRC sites. The species compositions of the aboveground vegetation of MRC and NMRC sites was significantly different with strong clustering by site type, while the seedbank compositions was not significantly different. Further, broad separation between the soil seedbank composition and extant vegetation of both MRC and NMRC sites was demonstrated. These results indicate that MRC and NMRC sites are similarly affected by seed dispersal/recruitment. However, processes such as environmental filtering may influence the germination and establishment of seedlings and perpetuate differences in species composition of MRC and NMRC rock outcrop communities.